Аннотированный указатель зарубежных периодических изданий, получаемых ВГБИЛ - Алексеев В. П.; Брагинская Э. В.; Виссарионова М. К.; Прохорова Р. В.; Шевченко Г. А.; Макаров А. А. (Москва, [Б. и.], 1979)
Исключено из фонда НТБ ТПУ